2015
DOI: 10.1126/scitranslmed.aac9511
|View full text |Cite
|
Sign up to set email alerts
|

Plasma AR and abiraterone-resistant prostate cancer

Abstract: AR gene aberrations are rare in prostate cancer prior to primary hormone treatment but emerge with castration resistance. To determine AR gene status using a minimally-invasive assay that could have broad clinical utility, we developed a targeted next-generation sequencing approach amenable to plasma DNA that covers all the AR coding bases and regions of the genome highly informative in prostate cancer. We here sequenced 274 plasma samples from 97 castration-resistant prostate cancer patients treated with abir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
411
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 396 publications
(448 citation statements)
references
References 33 publications
32
411
2
3
Order By: Relevance
“…The median progressionfree survival of patients with AR gene gain was 2.8 vs 9.5 months for those without AR gene gain (P < 0.0001), whereas the median OS was 5.0 months for the former and 21.9 months for the latter (P < 0.0001). Similarly, two other studies (Carreira et al 2014, Romanel et al 2015 showed that AR copy number gain, analyzed by nextgeneration sequencing, was associated with resistance to abiraterone in CRPC patients.…”
Section: Ar-targeting Therapy In Er-negative/her2-positive Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…The median progressionfree survival of patients with AR gene gain was 2.8 vs 9.5 months for those without AR gene gain (P < 0.0001), whereas the median OS was 5.0 months for the former and 21.9 months for the latter (P < 0.0001). Similarly, two other studies (Carreira et al 2014, Romanel et al 2015 showed that AR copy number gain, analyzed by nextgeneration sequencing, was associated with resistance to abiraterone in CRPC patients.…”
Section: Ar-targeting Therapy In Er-negative/her2-positive Bcmentioning
confidence: 99%
“…Point mutations within the AR LBD have also been implicated in the development of resistance to enzalutamide (F876L, F877L) and abiraterone (T878A and L702H) (Joseph et al 2013, Korpal et al 2013, Carreira et al 2014, Azad et al 2015, Romanel et al 2015.…”
Section: :10mentioning
confidence: 99%
“…In addition, an understanding of the mechanisms behind abiraterone (Romanel et al 2015) and enzalutamide resistance (Claessens et al 2014), and whether this is linked to altered androgen and oestrogen metabolism, will be required before the next big step is taken towards development of endocrine therapy for prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with hormonal therapy in CRPC patients positively selects for mutations in the AR ligand-binding domain, several of which can be activated by glucocorticoids (Carreira et al 2014, Romanel et al 2015. This is very relevant to abiraterone-treated patients for two reasons.…”
Section: Glucocorticoids and Precursorsmentioning
confidence: 99%